Impact of Government Capital Expenditure on Poverty Levels in Maluku - Teddy Christianto Leasiwal (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2021)
Fiscal policy is an inseparable part of macroeconomic policy both in the short and long term. Fiscal policy is set to achieve economic growth. The policy of opening faucets and stimulating the investment climate is expected to be able to create job opportunities which in turn increase income, thereby reducing poverty Expansive policy also means that government spending aims at infrastructure development and labor-intensive projects that will reduce unemployment and poverty in Maluku Although government capital expenditures continue to increase, economic growth in several districts / cities has not shown the same level of economic growth. This study measures two variables, namely Government Investment and Government Consumption. To identify it, an analysis was carried out using the linear regression method with the type of panel data. The regression results found that government investment has a very positive and significant effect with a siginfikansi level of 0.04 on the poverty level in Maluku while for the Government consumption variable, it also has a positive and significant effect of 0.03 on poverty.